Cellular schwannoma: a rare spinal benign nerve-sheath tumor with a pseudosarcomatous appearance: case report - José Alberto Landeiro; Carlos Henrique Ribeiro; Alexandre C. Galdino; Elizabeth Taubman; Alfredo J. Guarisch (Arquivos de Neuro-Psiquiatria)
We report a case of cellular schwannoma, a rare benign nerve-sheath tumor in a 27 year-old woman. It was presented as a voluminous lesion in the paraspinal region that caused lumbar vertebral body destruction. These features, in association to the microscopic aspects of a hypercellular, pleomorphic neoplasm may lead to a false impression of a malignant tumor. Therefore, it is important to have an accurate examination to confirm the benign nature of this tumor thus avoiding unnecessary therapy.